PELATIHAN PRODUK OLAHAN SINGKONG SEBAGAI WIRAUSAHA MANDIRI SISWA SMK MUHAMMADIYAH 3 MOJOAGUNG - Dinaloni, Diah; Muktiadji, Henky; Amaliah, Ninik (Yayasan Education and Social Center, 2025)
Utilization of local food ingredients such as cassava offers great opportunities in the development of culinary products that are economical, nutritious, and marketable. One interesting form of processing with business prospect is caasave nuggets. This product not only seves as healthy snack alternative, but also has a wide market potential, particularly among young cosumers and local communities. The practical training on cassava nugget making for students of SMK Muhammadiyah 3 Mojoagung is held as a form of integration between productive learning and strangtheninh entrepreneurial values based on local potential. The activity is expected to foster students’creativity in creating processed products with market value, while also encouraging the emergence of independent business ideas that are relevant to the needs of the surrounding community. The implementation method of PkM consists of: (1) Preparation stage, starting with exposition of local potential identification, especially cassava as an abundant and cheap raw material; (2) The implementation stage, where students are given material about entrepeneurship, the concept of creative products, market analysis, and principles of simple business management, which is delivered interactively though case studies, group discussions, and audiovisual media. Subsequently, students practice directly processing cassava into a culinary product, namely cassava nuggets; (3) Evaluation stage, in this evaluation stage, the product is assessed based on taste and appearance. The result is that students are able to make cassava nuggets woth a texture and flavor that meet the standards, students contribute to discussion and hands on practice in making cassava nuggets, and the products from practice are assessed by the PkM team dan receive positive feedback. From the training on processed cassava products as independent entrepreneurs for students of SMK Muhammadiyah 3 Mojoagung, it is recommended to collaborate and provide guidance involving UMKM, and to hold product demonstrations and school bazaars as a market trial